Clinical Evaluation of Faricimab in Real-World Diabetic Macular Edema in India- A Multicenter Observational Study - Chakraborty D; Das S; Maiti A; Sinha TK; Das A; Sheth J; Boral SK; Mondal S; Nandi K (Clinical Ophthalmology)
Debdulal Chakraborty,1 Sudipta Das,2 Aniruddha Maiti,3 Tushar Kanti Sinha,1 Arnab Das,1 Jay Sheth,4 Subhendu Kumar Boral,1 Soumen Mondal,1 Krishnendu Nandi2 1Disha Eye Hospitals, Kolkata, India; 2Nethralayam Superspeciality Eye Care, Kolkata, India; 3Global Eye Hospitals, Kolkata, India; 4Department of Retina Services, Shantilal Shanghvi Eye Institute (SSEI), Mumbai, IndiaCorrespondence: Debdulal Chakraborty, Department of Vitreo-retinal Services, Disha Eye Hospitals, 88 Ghosh Para Road Barrackpore, Kolkata, West Bengal, 700120, India, Tel +91 33 6636 0000, Email devdc@rediffmail.comPurpose: To evaluate the efficacy of faricimab in real-world clinical settings in India for treating diabetic macular edema (DME) in treatment-naïve and recalcitrant eyes.Patients and Methods: This retrospective study involved 39 eyes (16 treatment-naive and 23 recalcitrant) treated with intravitreal faricimab at four centers in India. Patients received three monthly loading doses followed by a pro-re-nata regimen, with outcomes measured for best-corrected visual acuity (BCVA), central macular thickness (CMT), intraretinal fluid (IRF), subretinal fluid (SRF), and hyperreflective foci (HRF).Results: Significant improvements in BCVA were observed in both treatment-naïve and recalcitrant groups, with greater gains in the naïve group (p< 0.001). Overall, BCVA improved from 0.48 logMAR to 0.27 logMAR (P< 0.001), and 59% of eyes gained more than 10 ETDRS letters and 41% gaining > 15 ETDRS letters. Both groups showed significant reduction in CMT, with the naïve group achieving greater reduction (P< 0.001). The overall CMT reduction was statistically significant at 6 months (P< 0.001). Resolution of IRF and SRF was achieved in both groups, with SRF reducing from 82.1% to 20.5% (P< 0.001) and IRF from 87.2% to 17.9% (P< 0.001). Significant reductions in HRF were also observed across both inner (P< 0.001) and outer retinal layers (P< 0.001). No ocular or systemic adverse events were reported.Conclusion: Faricimab treatment resulted in significant improvements in visual acuity and anatomical outcomes in both treatment-naïve and recalcitrant DME eyes, highlighting its potential as a valuable therapeutic option in diverse clinical settings. Further real-world studies are warranted to establish long-term efficacy and safety.Keywords: diabetic macular edema, anti VEGF, faricimab